2018
DOI: 10.1051/matecconf/201819503009
|View full text |Cite
|
Sign up to set email alerts
|

Expansive soil improvement of Glagahagung village, Purwoharjo sub-district, Banyuwangi district, which is chemically stabilized

Abstract: Abstract. Expansive soil can be easily found at Purwoharjo, a sub-district of Banyuwangi. Swelling and shrinkage behavior of the soil is usually referred to by the local community as a "moving soil" phenomenon. It causes cracks on a number of buildings which is a major issue in that area. Various methods of expansive soil stabilization are available. This work intends to lay comparisons on stabilizations using wood charcoal powder and salt. The stabilizing materials are mixed with the soils under different pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…While the kaolinite-rich material shows GI variations above the 0.6% concentration, it appears that GI occurs immediately with the salinization of the smectite-rich material. Data and findings in the present research follow those obtained by Putra et al (2018), in which expansive soils have their IG markedly decreased.…”
Section: The Role Of Electrochemistry and Mineralogy In The Geotechnical Behavior Of Salinized Soilssupporting
confidence: 90%
See 1 more Smart Citation
“…While the kaolinite-rich material shows GI variations above the 0.6% concentration, it appears that GI occurs immediately with the salinization of the smectite-rich material. Data and findings in the present research follow those obtained by Putra et al (2018), in which expansive soils have their IG markedly decreased.…”
Section: The Role Of Electrochemistry and Mineralogy In The Geotechnical Behavior Of Salinized Soilssupporting
confidence: 90%
“…Sen et al (2016) also found a decrease in PI values in kaolinitic and smectitic materials in experiments with saline solutions of NaCl, CaCl 2 , and MgCl 2 . Putra et al (2018) also showed a marked AI reduction against NaCl concentration increase.…”
Section: The Role Of Electrochemistry and Mineralogy In The Geotechnical Behavior Of Salinized Soilsmentioning
confidence: 90%